2021
DOI: 10.1073/pnas.2016265118
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tetracycline combinations as EphB1 tyrosine kinase inhibitors for treatment of neuropathic pain

Abstract: Previous studies have demonstrated that the synaptic EphB1 receptor tyrosine kinase is a major mediator of neuropathic pain, suggesting that targeting the activity of this receptor might be a viable therapeutic option. Therefore, we set out to determine if any FDA-approved drugs can act as inhibitors of the EphB1 intracellular catalytic domain. An in silico screen was first used to identify a number of tetracycline antibiotics which demonstrated potential docking to the ATP-binding catalytic domain of EphB1. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 74 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…The crystal structures of EphB1 (PDB code: 6UMW, Resolution: 1.98 Å) [41], EphB2 (PDB code: 2HEN, Resolution: 2.60 Å) [42], EphB3 (PDB ID: 5L6P, Resolution: 2.26 Å) [15], EphB4 (PDB ID: 3ZEW, Resolution: 2.50 Å) [43], VEGFR2 (PDB code: 3VHE, Resolution: 1.55 Å) [44], Aurora A (PDB code: 2X6E, Resolution: 3.35 Å) [45], HER2 (PDB code: 3PP0, Resolution: 2.25 Å) [46] and CDK2 (PDB code3PY0, Resolution: 1.75 Å) [47] were downloaded from protein data bank (www.pdb.org, accessed date: 18 April 2021). To ensure the validity of the downloaded crystal structures, PROCHECK server was employed to generate a Ramachandran plot for all four downloaded crystal structures to ensure their validity [30].…”
Section: Protein Preparationmentioning
confidence: 99%
“…The crystal structures of EphB1 (PDB code: 6UMW, Resolution: 1.98 Å) [41], EphB2 (PDB code: 2HEN, Resolution: 2.60 Å) [42], EphB3 (PDB ID: 5L6P, Resolution: 2.26 Å) [15], EphB4 (PDB ID: 3ZEW, Resolution: 2.50 Å) [43], VEGFR2 (PDB code: 3VHE, Resolution: 1.55 Å) [44], Aurora A (PDB code: 2X6E, Resolution: 3.35 Å) [45], HER2 (PDB code: 3PP0, Resolution: 2.25 Å) [46] and CDK2 (PDB code3PY0, Resolution: 1.75 Å) [47] were downloaded from protein data bank (www.pdb.org, accessed date: 18 April 2021). To ensure the validity of the downloaded crystal structures, PROCHECK server was employed to generate a Ramachandran plot for all four downloaded crystal structures to ensure their validity [30].…”
Section: Protein Preparationmentioning
confidence: 99%
“…The energy-minimized drugs underwent protonation states to add the missing hydrogens for proper ionization states. MOE docking module used to evaluate the favorable binding conformers based on London dG scoring method to estimate energy profile based on the binding affinity with respect to hydrophobic-hydrophobic interactions, hydrogen bonding, pi-pi interactions, and ionic interactions [57,58]. Each drug gave 10 possible docked poses.…”
Section: Methodsmentioning
confidence: 99%
“…A common ceftriaxone dose was used for this study [ 48 ] Demeclocycline Chlortetracycline Antibiotics (tetracyclines) In silico screen, capsaicin-induced pain model, CFA model, formalin model in mice Combination of chlortetracycline 7 mg/kg/day PO and demeclocycline 20 mg/kg/day PO 3 days in advance Chlortetracycline binds and inhibits the EphB1 activation and reduces phosphorylation in the brain, spinal cord, and dorsal root ganglion (DRG) Combination of minocycline, chlortetracycline and demeclocycline reduces mechanical and thermal hypersensitivity. Likely off-target due to high dose Chlortetracycline is used ophthalmic or local (ointment) 1–3% (w/w) Demeclocycline is used at 100 mg orally/d [ 36 ] Fingolimod S1P-modulator Cancer-induced bone pain (CIBP) model in mice 1 mg/kg/day IP or SC (continuous infusion with osmotic minipump) for 7 consecutive days Fingolimod treatment reduces flinching and guarding behavior. Possibly off-target due to high dose 0.5 mg PO once daily [ 55 ] Mouse model of multiple sclerosis-induced neuropathic pain (EAE model) 0.1–1 mg/kg IP daily from days 15–34 and 45–52 post-EAE induction; 0.001–1 mg/kg IP daily from days 15–37 post-EAE induction Reduces mechanical hypersensitivity and cold allodynia, reduces pERK activation in the spinal cord via S1P1R and reduces the number of activated spinal microglia and astrocytes.…”
Section: Targeting Neuroinflammation With Approved Drugsmentioning
confidence: 99%
“…A recent study identified that demeclocycline, chlortetracycline, and minocycline bind and inhibit the tyrosine kinase ephrin type-B receptor 1 (EphB1) in the brain, spinal cord, and dorsal root ganglia (DRG). Treating mice with a combination of these three tetracyclines caused a reduction of mechanical and thermal hypersensitivity in capsaicin-, CFA- and formalin-induced pain [ 36 ]. Mechanistically, minocycline seems to reduce the production of reactive oxygen species in microglia and the release of proinflammatory and prologetic cytokines and chemokines, such as TNFα, IL-1β, and CXCL1 [ 37 ] (Fig.…”
Section: Targeting Neuroinflammation With Approved Drugsmentioning
confidence: 99%
See 1 more Smart Citation